Malnutrition mitigation and community empowerment through the sustainable food reserve programme in Indonesia. Issue 1 (2nd January 2021) - Wijaya, Andy Fefta; Kuntariningsih, Apri; Sarwono, Sarwono; Suryono, Agus
ABSTRACT: This article analyses the implementation of a sustainable food reserve programme in mitigating the malnutrition and empowering vulnerable communities in East Java, Indonesia. Structural equation modelling and sustainable livelihood approach were adopted as analytical tools. Data were compiled from the reports of executing institutions, and primary data were collected from stakeholders. Results show that the programme was successful in mitigating vulnerable communities from malnutrition, and empowering them to improve their livelihoods. Despite some constraints, the programme improved communities' consumption patterns in ways that guaranteed balanced food consumption and enhanced five livelihood capitals.